A smart tumor targeting peptide–drug conjugate, pHLIP-SS-DOX: synthesis and cellular uptake on MCF-7 and MCF-7/Adr cells. (12th June 2016) - Song, Qin; Chuan, Xingxing; Chen, Binlong; He, Bing; Zhang, Hua; Dai, Wenbing; Wang, Xueqing; Zhang, Qiang
Abstract: Doxorubicin (DOX) is a potent anticancer drug for the treatment of tumors, but the poor specificity and multi-drug resistance (MDR) on tumor cells have restricted its application. Here, a pH and reduction-responsive peptide–drug conjugate (PDC), pHLIP-SS-DOX, was synthesized to overcome these drawbacks. pH low insertion peptide (pHLIP) is a cell penetrating peptide (CPP) with pH-dependent transmembrane ability. And because of the unique cell membrane insertion pattern, it might reverse the MDR. The cellular uptake study showed that on both drug-sensitive MCF-7 and drug-resistant MCF-7/Adr cells, pHLIP-SS-DOX obviously facilitated the uptake of DOX at pH 6.0 and the uptake level on MCF-7/Adr cells was similar with that on MCF-7 cells, indicating that pHLIP-SS-DOX had the ability to target acidic tumor cells and reverse MDR. In vitro cytotoxicity study mediated by GSH-OEt demonstrated that the cytotoxic effect of pHLIP-SS-DOX was reduction responsive, with obvious cytotoxicity at pH 6.0; while it had poor cytotoxicity at pH 7.4, no matter with or without GSH-OEt pretreatment. This illustrated that pHLIP could deliver DOX into tumor cells with acidic microenvironment specifically and could not deliver drugs into normal cells with neutral microenvironment. In summary, pHLIP-SS-DOX is a promising strategy to target drugs to tumors and provides a possibility to overcome MDR.